SHEAR CAPACITY OF SUSTAINABLE LIGHT WEIGHT CONCRETE BEAMS - Q. Makhool, Aseel; K. Alsaraj, Wissam; A. Zghair , Luma (Journal of Engineering and Sustainable Development, 2021)
This Lightweight concrete is one of the important types familiar of concrete, as the local stone Attapulgite was used as aggregate after treating it with a solution of minors, then it was used in pouring five -reinforced concrete beams by adding steel fiber and iron filing separately with two percentages of 0.5 and 1, these beams were examined to determine the shear capacity. The results showed that iron filing by 1% improve the mechanical properties of concrete and similar to that of using steel fibers, but with a minimum effect. The results also showed that adding 1% of steel filing improves the maximum shear resistance and the first cracking resistance of the concrete by 38%.